Lahan Basah dan Arkeologi Nusantara - Muh. Fadlan S. Intan; Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2008)
AbstractReferring to the assumption that the technology gives deep influence to the human ability to adapt the environment, we have found that the research result could describe the influence of environment to human being in the simplest level in cultural evolution. In line with that, the role of human in changing the environment will increase in parallel with the development of technology. As one of environmental form, there’s a wide wetland in Indonesia which is known as an wetland country and people also depend on it. Wetland has an importand value in contributing the biological variance, world climate regulator, source of food, etc that give the benefit to the human’s life and others. It’s not surprising that there’s lot of archaelogical sites on wetland area.